2005
DOI: 10.1002/cbic.200400316
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Novel Landomycins M and O through Targeted Gene Disruption

Abstract: Two genes from Streptomyces cyanogenous S136 that encode the reductase LanZ4 and the hydroxylase LanZ5, which are involved in landomycin A biosynthesis, were characterized by targeted gene inactivation. Analyses of the corresponding mutants as well as complementation experiments have allowed us to show that LanZ4 and LanZ5 are responsible for the unique C-11-hydroxylation that occurs during landomycin biosynthesis. Compounds accumulated by the lanZ4/Z5 mutants are the previously described landomycin F and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 30 publications
4
56
0
1
Order By: Relevance
“…The trideoxyhexose NDP-l-rhodinose is formed by subsequent 3-deoxygenation (SaqQ; 27), 5-epimerization (SaqZ1; 19), and 4-ketoreduction (SaqZ3; 26). The biosynthesis of NDP-d-olivose is accomplished by a 4-ketoreduction that is catalyzed by SaqR (29). The final steps toward NDP-l-2-deoxyfucose are 5-epimerization (SaqZ1; 19) and 4-ketoreduction (SaqZ3; 26).…”
Section: Resultsmentioning
confidence: 99%
“…The trideoxyhexose NDP-l-rhodinose is formed by subsequent 3-deoxygenation (SaqQ; 27), 5-epimerization (SaqZ1; 19), and 4-ketoreduction (SaqZ3; 26). The biosynthesis of NDP-d-olivose is accomplished by a 4-ketoreduction that is catalyzed by SaqR (29). The final steps toward NDP-l-2-deoxyfucose are 5-epimerization (SaqZ1; 19) and 4-ketoreduction (SaqZ3; 26).…”
Section: Resultsmentioning
confidence: 99%
“…[12] For example, the gene lndM2 was found to encode a bifunctional oxygenasereductase that is responsible for the introduction of the 6-O atom in LaE, [11] and lndZ4/Z5 were found to be responsible for the addition of the 11-OH group in LaE. [10,13] Most recently, inactivation of the lndE gene in S. globisporus led to the accumulation of prejadomycin (2,3-dehydro-UWM6), which proved that oxygenase LndE is responsible for the generation of the p-quinone moiety through oxidation of the 12-position. [14] Thus, all oxygenases that incorporate oxygen atoms into the landomycin aglycon have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The pair of genes lndZ4 and lndZ5, was declared to be respon sible for the 11 hydroxylation that occurs during landomycin E (2) biosynthesis [13]. The authors also showed that hydroxylation at position 11 is not dependent on the length of the side chain and may occur at different stages during landomycin A biosynthesis.…”
Section: Methodsmentioning
confidence: 98%
“…This opportunity encouraged us to introduce this pair of genes, encoding hydroxylase and reductase to S. fradiae Tu2717, as urdamycins just lack 11 hydroxyl. Interestingly, landomycin F, was approximately threefold less active against the MCF 7 breast cancer cell line than its correspon ding 11 hydroxy analogue, landomycin D [13]. We brought lndZ4/Z5 consisting of the plasmid рКС1218Е ВХ3 (Fig.…”
Section: Methodsmentioning
confidence: 99%